Utilization of Near Infrared Reflectance Spectroscopy (NIRS) to quantify the impact of earthworms on soil and carbon erosion in steep slope ecosystem: a study case in northern Vietnam - Jouquet, Pascal; Henry des Tureaux, Thierry; Mathieu, J.; Doan Thu, Thuy; Tran Duc Toan; Orange, Didier (Elsevier, 2010)
This work focuses on a new approach to quantify the effects of above-ground earthworm's activity on soil erosion in steep slope ecosystems such as in Northern Vietnam. In these areas and in many others in the world, soil erosion becomes a major issue while the factors that determine it are still misunderstood. Earthworm's activity is believed to influence soil erosion rate, but we are still unable to precisely quantify their contribution to soil erosion. In this study, we used Near Infrared Reflectance Spectroscopy (NIRS) to quantify the proportion of soil aggregate in eroded soil coming from earthworm activity. This was done by generating NIRS signatures corresponding to different soil surface aggregates (above-ground soil casts produced by earthworms vs. surrounding topsoil). In order to test the proposed approach, we compared the NIRS-signature of eroded soil sediments to those of earthworms' casts and of the surrounding soils. Our results strongly supported that NIRS spectra might be used as "fingerprints? to identify the origin of soil aggregates. Although earthworms are generally assumed to play a favorable role in promoting soil fertility and ecosystem services, this method shows that cast aggregates constitute about 36 and 77% of sediments in two tropical plantations, Paspalum atratumand Panicum maximum plantations, respectively. In light with these results, we estimated that earthworms led to an annual loss of 3.3 and 15.8 kg of carbon ha-1 yr-1, respectively in P. atratum and P. maximum agroecosystems.